Improving Energy Efficiency in Satellite-to-Ground Communications With Multiple Reflecting Intelligent Surfaces - Khalil, Muhammad I.; Lin, Jiao; Wang, Ke (IEEE transactions on green communications and networking, 2024)
This study introduces two novel approaches to enhance the energy efficiency of satellite-to-ground communication systems by using multiple Reconfigurable Intelligent Surfaces (RISs) on terrestrial platforms. We explore scenarios in both ideal environments (IE), which assume no shadowing loss, and non-ideal environments (NIE), which consider practical environmental influences such as shadowing. In the IE scenario, energy efficiency is optimized through a dual strategy: first, by maximizing power reception through precise phase shift adjustments of each RIS element; second, by employing Selective Diversity combined with Binary Particle Swarm Optimization (BPSO) to minimize power consumption. This theoretical benchmark in the IE scenario sets the stage for the NIE scenario, where the Adaptive Moment Estimation (Adam) optimization algorithm is employed to systematically enhance energy efficiency under real-world operational conditions. Simulation results demonstrate the significant potential of the proposed methods for energy savings in satellite-RIS systems.